Ethnography of Instituto Casa da Cidade’s Roda de Choro - Rosa, Luciana Fernandes (2019)
This paper presents an ethnography of a roda de choro2 that occurred in July, 2016, at The Casa da Cidade Institute, located in Vila Madalena, São Paulo. The roda in question, at the time held monthly, was organized by an elderly musician in the scene of the São Paulo choro and brought together amateur musicians, professionals, students and listeners. Aspects of the musical making of the roda and the profile of its participants from the perspective of some authors related to ethnomusicology were observed, among them Ruth Finnegan, Thomas Turino, John Blacking and Etienne Wenger, through participant observation and interviews with attendees of the event. It is concluded that the roda has characteristics that differ from other rodas de choro of the capital, to have the participation of amateur and professional musicians in a democratic and welcoming environment, and for evidencing aspects of rescue of the personal history of the musicians.